Investigation on the effect of reaction parameters to the palm oil cross-metathesis using 1-octene and ruthenium based catalyst - Thangavel, Mythili (2022)
The use of palm oil-derived polyol for the production of polyurethane is restricted because of its low-hydroxyl value that causes imperfect polyurethanes network. The polyol with desired hydroxyl value could be produced from palm oil if it is chemically transformed using cross metathesis (CM) into olefin and ester products with terminal double bonds prior to the production of polyols. The plant oil CM process using ethylene has been hampered by its poor selectivity and low yield due to the catalyst deactivation and its catalytic intermediate (ruthenium methylidene), in addition to the undesired self-metathesis reaction. The study aimed to identify the best operating condition of the palm oil CM using 1-octene, which is believed to supress the formation of side products and unwanted catalytic intermediate, allowing the ruthenium-based Hoveyda Grubbs second generation catalyst (2nd HGC) to maintain its activity and stability. The effect of different parameters on cross-metathesis of palm oil performance was carried out using one factorial at time (OFAT) in a batch system. The changes in parameters like reaction times, temperatures, reactant molar ratios of 1-octene to palm oil (MOC/PO)/molar ratio of 1-octene to triolein (MOC/TR) and 2nd HGC catalyst loadings were correlated to the triolein conversion, 1-decene yield and selectivity of 1-decene calculated based on the amount of the reaction products. The products such as 1-decene and glyceryl tri-9-decenoate were quantified using Gas Chromatography-Mass Spectrometry (GC-MS). Proton Nuclear Magnetic Resonance (1H NMR) analysis was used to verify the structural changes of palm oil triglyceride to other olefins in the reaction mixture. The maximum conversion, yield and selectivity were obtained when the palm oil was cross-metathesised with MOC/TR of 8 and catalyst loading of 5 ppm occurred at 343 K for 2 h which resulted in 97.78% of triolein conversion, 293.36% of 1-decene yield. After three consecutive catalytic tests carried out at best operating condition, the insignificant decline in the reaction performance evidenced that the 2nd HGC catalyst still remained active and stable. It was also found that the power-law model well predicted the concentration profile of the cross-metathesis of palm oil using 1-octene, estimating activation energy of 22583 J/mol. This study developed a new technically feasible process for adding value to palm oil, enable the use of palm oil as a feedstock for the production of polyol with required hydroxyl value.